From Paris and Beijing to Washington and Brasilia the grand design of capital cities and the early plans for Quezon City - Boquet, Yves (2016)
Political leaders have always sought to build monumental capitals, with earlier designs influencing those of later cities. The Western design that revolved around a central axis of power became evident in some Asian capitals, although cities in the Chinese cultural realm differed in shape but nonetheless had its own axis of power. This article provides a typology of capital cities and from this perspective it explores the design of the newly created capital of Quezon City in the late 1930s. Quezon City's design embraced some design ideas from elsewhere, but it remained unique. However, the design was not realized entirely.
Keywords: Capitals (Cities); Urban planning; Manila City; Quezon City